Analysis of Fraud in Transactions on Shopee: A Fiqh Muamalah Perspective Using the Fraud Triangle Theory - Syamsuri Syamsuri; Asti Lutfiah (Al-Mustashfa: Jurnal Penelitian Hukum Ekonomi Syariah, 2025)
This study analyzes fraud in Shopee transactions using the fraud triangle theory and the perspective of fiqh muamalah. Fraudulent activities in the Shopee marketplace, such as scams and deceitful seller practices, contradict Islamic principles, resulting in material and non-material losses. Fiqh muamalah, as a foundational framework for Islamic trade, strictly prohibits fraudulent practices that cause harm or injustice. The study employs a qualitative approach, utilizing content analysis of case studies on Shopee fraud. The findings reveal that fraud on Shopee arises due to economic pressure as a trigger for fraudulent behavior, opportunities created by weak regulatory frameworks, and the rationalization of fraud stemming from a lack of public awareness about online transaction rules. From the perspective of fiqh muamalah, these factors result in injustice and violate fundamental principles such as honesty (sidq), trustworthiness (amanah), and the prevention of harm (la darara wa la dirar). The study highlights the need to address these issues to align online transactions with Islamic ethical standards.Keywords: Fraud Triangle; Transactions, Shopee; Fiqh Muamalah